RESPON PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU TERHADAP PEMBERIAN PUPUK BIOKOMPLEKS DAN INTERVAL PENGAPLIKASIAN ATONIK - Putri, Citra; Sugiarto; Sugianto, Agus (Universitas Islam Malang, 2025)
The use of inorganic fertilizers and PGR can cause problems for the environment and plant growth. The purpose of this study was to determine the effect of biocomplex fertilizer combined with Atonic application interval on the growth and yield of green mustard. The research was conducted in the Greenhouse of the Integrated Field Laboratory University of Islam Malang, Kebonagung, Malang Regency from June-August 2024. This research was designed using a Randomized Group Design arranged factorially, there were 2 factors repeated 3 times. The first factor is biocomplex fertilizer’s dose, consisting of 4 levels: Control, 5 tons/ha, 10 tons/ha, 15 tons/ha. The second factor is the Atonic application interval, consisting of 4 levels: Control, 5 days, 10 days, 15 days. Data were then subjected to F test (ANOVA), DMRT 5% and regression correlation test. Interaction between treatments effects the leaf area with the best treatment is dose of 5 tons/ha + 5 days interval. Biocomplex fertilizer’s dose effect the total fresh weight, plant dry weight, economic fresh weight, vitamin C, and total soluble solids. The best results is dose of 5 tons/ha. The interval of Atonic application affects the economic fresh weight with the best treatment is 15 days application interval.